Experiences and outcomes of women with bleeding in early pregnancy presenting to the Emergency Department: An integrative review. (March 2022) - Trostian, Baylie; Curtis, Kate; McCloughen, Andrea; Shepherd, Ben; Munroe, Belinda; Davis, Warren; Hirst, Elizabeth; Tracy, Sally K.
Abstract: Background: Bleeding in early pregnancy occurs in approximately a quarter of all pregnancies and is a common reason for presentation to the Emergency Department (ED). This review combined current knowledge about experiences, interventions, outcomes and frequency of women presenting to the ED with per vaginal (PV) bleeding in the first 20 weeks of pregnancy. Methods: This integrative literature review was conducted using electronic database and hand searching methods for primary research published from 2000; followed by screening and appraisal. Articles were compared and grouped to identify characteristics and patterns that guided the synthesis of categories. Results: Forty-two primary research articles met inclusion criteria. Four main categories related to experiences and outcomes of women with bleeding in early pregnancy presenting to the ED were identified: presentation frequency and characteristics; women and their partners' experiences in the ED; interventions and treatments; patient and health service outcomes. Conclusions: Negative and often frustrating experiences are reported by women experiencing PV bleeding, their partners and ED healthcare providers. While strategies such as early pregnancy assessment services contribute to improved outcomes, the availability of these services vary. Further research is needed to identify specific needs of this group of women and their partners, and the staff providing their care in the ED, to inform strategies for improved quality of care.